Sacje’s role and function: A membership survey - Southerland, Mittie D. (American journal of criminal justice, 1984)
The Southern Association of Criminal Justice Educators (SACJE) is a regional professional organization which was developed to improve professionalism in criminal justice. In recent years the organization seemed to loose its focus and was having membership and budgetary problems. The authors, in an attempt to understand the feelings of members and former members, surveyed current and prior members of SACJE. The results of the survey are presented with recommendations for action by the SACJE Executive Board. Several areas of consensus were evident. The membership wants SACJE to continue to exist. The role of the organization is to promote better criminal justice education and to disseminate new criminal justice information. The membership wants annual meetings and the Southern Journal of Criminal Justice published twice yearly. They also want voting by mail on all major issues and elections. All other voting should be conducted at a business meeting on the second day of a three day annual meeting.